REPETISI PADA KUMPULAN PUISI PEREMPUAN WALI KOTA KARYA SURYATATI A MANAN - Zulfadhli, Muhammad; Charlina, Charlina; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe tittle of this research is repetition on collection Perempuan Wali Kota poetry by Suryatati A manan. The purpose of research is to analyze the kind, function and repetition meaning . This research is a qualitative study with descriptive method. The data such as words, pharases, clauses, and sentences. The data of this research are 60 datas. The result of this research found the kind of repetition, that are (10) epizeukis, (4) tautotes, (10) anaphora, (10) epistrofa, (1) simploke, (10) mesodilopsis, (2) epanalepsis, (10) anadiplosis and new (2) epistrofa introgratifa, and (1) epistropfa numerelia repetition. Futhermore, the function of repetition that are (25) assertive to explain, (6) notices, (1) suggest, (2) boast, (2) complain, (1) prosecute, and (1) reporting. The function of directive that are (5) command, (1) pleading, (1) suggesting, and (3) advising. The function of commisive (1) ineffective. Identify Ekspression to explain about praise (6) and identify declarative as the question to explain about name (4) and (1) appointing. The meaning of repetition that are (14) cognitive meaning or referential, (9) emotive or pictoral, (4) construction, (5) grammatical, (8) proposition, (11) central meaning and (9) idiomatic meaning. The dominant kind of repetition found is epizeukis, anaphora, epistrofa, mesodilopsis, and anadiplosis repetition (10), and assertive statement is dominant repetition function found (25). The dominant meaning of repetition found that cognitive of referential (14). The element of aesthethics contens dominate on collection Perempuan Wali Kota poetry by Suryatati A Manan. Keywords: repetition, kind repetition, function repetition, repetition meaning, poetry.